ANALYSIS OF THE TRADE AND INVESTMENT CHANNELS AS WAYS TO EXPAND AND ENHANCE THE ECONOMIC COOPERATION OF THE REPUBLIC OF KOREA WITH THE EAEU COUNTRIES - Dok Hee OH; Kyung Sook GIL (Eastern European Journal of Regional Studies)
Expanding economic cooperation with the EAEU is of great importance to the Government of the Republic of Korea, which is focusing on providing new drivers of economic growth through expanded trade with various countries and groups of countries, including the Eurasian region. Economic cooperation between the Republic of Korea and the EAEU has the potential to promote mutually beneficial development in the long term as both regions are forming complementary industrial complexes. International competitiveness can be ensured through bilateral economic cooperation based on the advanced industrial technologies of the Republic of Korea, as well as energy and mineral resources, which are the main production factors of the EAEU countries. Moreover, in the current economic situation of the Republic of Korea, where it is necessary to reduce trade dependence on China, expanding cooperation with the EAEU is becoming a key aspect of its further economic development.